Immunomodulatory effects of tick saliva on dermal cells exposed to Borrelia burgdorferi, the agent of Lyme disease. Issue 1 (December 2016) - Scholl, Dorothy; Embers, Monica; Caskey, John; Kaushal, Deepak; Mather, Thomas; Buck, Wayne; Morici, Lisa; Philipp, Mario
Abstract Background The prolonged feeding process of ixodid ticks, in combination with bacterial transmission, should lead to a robust inflammatory response at the blood-feeding site. Yet, factors present in tick saliva may down-regulate such responses, which may be beneficial to spirochete transmission. The primary goal of this study was to test the hypothesis that tick saliva, in the context ofBorrelia burgdorferi, can have widespread effects on the production of immune mediators in skin. Methods A cross-section of tick feeding on skin was examined histologically. Human THP-1 cells stimulated withB. burgdorferi and grown in the presence or absence of tick saliva were examined by human DNA microarray, cytokine bead array, sandwich ELISA, and qRT-PCR. Similar experiments were also conducted using dermal fibroblasts. Results Tick feeding on skin showed dermal infiltration of histiocytes and granulocytes at the bite location. Changes in monocytic transcript levels during co-culture withB. burgdorferi and saliva indicated that tick saliva had a suppressive effect on the expression of certain pro-inflammatory mediators, such as IL-8 (CXCL8) and TLR2, but had a stimulatory effect on specific molecules such as the Interleukin 10 receptor, alpha subunit (IL-10RA), a known mediator of the immunosuppressive signal of IL-10. Stimulated cell culture supernatants were analyzed via antigen-capture ELISA and cytokine bead array for inflammatory mediator production. Treatment of monocytes with saliva significantly reduced the expression of several key mediators including IL-6, IL-8 and TNF-alpha. Tick saliva had an opposite effect on dermal fibroblasts. Rather than inhibiting, saliva enhanced production of pro-inflammatory mediators, including IL-8 and IL-6 from these sentinel skin cells. Conclusions The effects of ixodid tick saliva on resident skin cells is cell type-dependent. The response to both tick and pathogen at the site of feeding favors pathogen transmission, but may not be wholly suppressed by tick saliva.